Expression profiling of lymphocyte plasma membrane proteins. - Peirce, M; Wait, R; Begum, S; Saklatvala, J; Cope, A (2004)
The physicochemical properties of plasma membrane proteins of mammalian cells render them refractory to systematic analysis by two-dimensional electrophoresis. We have therefore used in vivo cell surface labeling with a water-soluble biotinylation reagent, followed by cell lysis and membrane purification, prior to affinity capture of biotinylated proteins. Purified membrane proteins were then separated by solution-phase isoelectric focusing and SDS-PAGE and identified by high-pressure liquid chromatography electrospray/tandem mass spectrometry. Using this approach, we identified 42 plasma membrane proteins from a murine T cell hybridoma and 46 from unfractionated primary murine splenocytes. These included three unexpected proteins; nicastrin, osteoclast inhibitory lectin, and a transmembrane domain-containing hypothetical protein of 11.4 kDa. Following stimulation of murine splenocytes with phorbol ester and calcium ionophore, we observed differences in expression of CD69, major histocompatibility complex class II molecules, the glucocorticoid-induced TNF receptor family-related gene product, and surface immunoglobulin M and D that were subsequently confirmed by Western blot or flow cytometric analysis. This approach offers a generic and powerful strategy for investigating differential expression of surface proteins in many cell types under varying environmental and pathophysiological conditions.